PENGGUNAAN SERAT KAYU PINUS PENGGANTI AGREGAT HALUS PADA CAMPURAN BETON MUTU NORMAL - Muhammad Yusuf; Liana Herlina; Akbar Triandhika Budiman; M. Mubaarak Alvian; Vindy Talahatu (INDONESIAN JOURNAL OF CONSTRUCTION ENGINEERING AND SUSTAINABLE DEVELOPMENT (CESD), 2022)
The use of concrete materials is an important element in sustainable development in every part of the world. Sustainable development must of course support various aspects, from the aspect of development to the maintenance of the development process to the establishment of a building. Departing from this, innovations emerged in which in terms of the development process, construction projects can run better, of course taking into account global climate conditions. The construction project itself certainly has an impact in the form of large-scale waste, as is the case with the construction of houses which still tend to use wood construction. Utilization of construction waste can be optimized by utilizing this waste. The material substitute is a form of innovation to make concrete that is different from normal concrete. Substitutes for this material vary from cement substitutes, fine aggregate to coarse aggregate. In this case sawdust became a substitute for fine aggregate with a 5% substitution. Mix design using SNI 7656:2012. The results obtained from concrete with a 5% substitution of wood fiber were lighter by 4% than normal concrete, but the compressive strength results also decreased by 10.7%